Diagnostic features of lung metastases differentiated thyroid cancer - T. M. Geliashvili; A. V. Vazhenin; E. B. Vasil’eva; N. G. Afanas’eva (Опухоли головы и шеи)
Background. The worldwide increasing incidence of thyroid cancer (TC) is mainly due to a rise in its major form of differentiated TC (DTC): papillary. Most patients with DTC have a good prognosis; 10-year survival overall rates are as high as 85 %, but not greater than 40 % in a group of patients with distant metastases. At the same time, the lung is the most frequent target for distant metastases, accounting for 70 % of all sites.Objective: to estimate and compare the capabilities of different diagnostic techniques to detect lung metastases of DTC. Materials and methods. The results of diagnosing lung metastases were retrospectively analyzed in 36 patients (33 women and 3 men; mean age 53 years) with DTC (29 patients with papillary TC and 7 with follicular TC) treated at the department of radiotherapy with systemic therapy, Chelyabinsk Regional Clinical Oncology Center from 2011 to 2014.Results. Chest X-ray could reveal pulmonary metastases in 13 (36 %) patients; lung pathology foci were absent in 23 (64 %) patients. 131I whole-body scintigraphy (WBS) proved to be of informative value in 24 (66.7 %) patients, it displayed no increased accumulation of the radiopharmaceutical in the lung of 12 (33.3 %) cases. Multislice spiral computed tomography (MSCT) of the chest was carried out in 22 (61 %) patients; out of them 21 (95.5 %) were found to have 1.4-to-20-mm lung cancer foci. 18Fluorodeoxyglucose (18FDG) positron emission tomography / computed tomography (PET / CT) was performed in 18 (50 %) patients, which showed 3–26-mm lung pathology foci in all the patents; out of them 16 (88.9 %) were detected to have metastases owing to the CT component of this method. Thus, the highest sensitivity was exhibited by MSCT (95.5 %), 18FDG PET / CT (100 % due to its CT component), and 131I WBS (66.7 %).Conclusion. When lung metastases of DTC are suspected, 1) chest X-ray should be used as a screening test; 2) 131I WBS should be performed in all patients; 3) MSCT of the chest is the gold standard for diagnosis; 4) 18FDG PET / CT should not be employed in routine practice.